The development of technology for production of zeolites from fly-ash from Troitskaya power plant - V. A. Snegirev; V. M. Yurk (Chimica Techno Acta)
The study examines the technology of processing fly ash from Troitskaya power plant for the production of zeolite. The paper presents the results of laboratory studies evaluating the suitability of fly ash from Troitskaya power plant for the production of zeolites and the development of the zeolite production process. Fly ash contains a small amount of heavy metals that can complicate processing, but contains a large amount of silicon oxide. The technology consists of high-temperature alkaline activation of fly ash and hydrochemical synthesis. The resulting powder has a specific surface area of 89.7 m2/g, determined by the BET method, and an average pore diameter of 0.345 μm. The static exchange capacity was 220 mg/g.